2016
DOI: 10.1111/pbi.12599
|View full text |Cite
|
Sign up to set email alerts
|

Increased salt tolerance with overexpression of cation/proton antiporter 1 genes: a meta‐analysis

Abstract: SummaryCation/proton antiporter 1 (CPA1) genes encode cellular Na+/H+ exchanger proteins, which act to adjust ionic balance. Overexpression of CPA1s can improve plant performance under salt stress. However, the diversified roles of the CPA1 family and the various parameters used in evaluating transgenic plants over‐expressing CPA1s make it challenging to assess the complex functions of CPA1s and their physiological mechanisms in salt tolerance. Using meta‐analysis, we determined how overexpression of CPA1s has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 62 publications
0
45
0
Order By: Relevance
“…The experimental evidence strongly supports a role in Na + transport under saline conditions, but more recent functional studies also point to basic roles of vacuolar NHXs under nonsaline conditions that go beyond stress acclimation . In addition to the compartmentation of Na + in the vacuole, NHXs may contribute to salinity tolerance by favorably adjusting cellular K + homeostasis under saline conditions (Ma et al, 2017;Wu et al, 2018).…”
mentioning
confidence: 99%
“…The experimental evidence strongly supports a role in Na + transport under saline conditions, but more recent functional studies also point to basic roles of vacuolar NHXs under nonsaline conditions that go beyond stress acclimation . In addition to the compartmentation of Na + in the vacuole, NHXs may contribute to salinity tolerance by favorably adjusting cellular K + homeostasis under saline conditions (Ma et al, 2017;Wu et al, 2018).…”
mentioning
confidence: 99%
“…Vacuolar and endosomal accumulation of K + , and concomitant lowering of cytoplasmic concentrations due to antiporter overexpression, would induce K + uptake mechanisms at the plasma membrane, resulting in maintenance of K + homeostasis in high salt conditions (Huertas et al, 2013;Jiang, Leidi, & Pardo, 2010;Leidi et al, 2009;Rodriguez-Rosales et al, 2008). Several other parameters are also affected, either as a direct consequence of enhanced ion accumulation or through separate pleiotropic mechanisms (Luca, Pardo, & Leidi, 2018;Ma et al, 2017). The studies showing a relationship between the transcript level of vacuolar and endosomal (Na + ,K + )/H + antiporters and salt tolerance were performed in transgenic plants overexpressing a plant gene.…”
Section: Vnx1 Is Involved In Vacuolar Ph Regulationmentioning
confidence: 99%
“…The protein AtNHX1 of Arabidopsis thaliana was initially described as a main source of salt tolerance in plants by driving Na accumulation into vacuoles (Apse et al , Zhang and Blumwald ). Many subsequent reports confirmed the ability of NHX‐like proteins from various origins to convey salt and drought tolerance to transgenic plants of several species, including crops (Ma et al ), but the underlying mechanism remained uncertain because salt tolerance not always correlated with enhanced Na accumulation (Jiang et al ). A meta‐analysis of a large number of publications reporting tolerance phenotypes of plants overexpressing exchangers of the cation/proton antiporter 1 family (CPA1, which includes NHX proteins) concluded that the transgenic effect on K status was generally more pronounced than on Na content (Ma et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Many subsequent reports confirmed the ability of NHX‐like proteins from various origins to convey salt and drought tolerance to transgenic plants of several species, including crops (Ma et al ), but the underlying mechanism remained uncertain because salt tolerance not always correlated with enhanced Na accumulation (Jiang et al ). A meta‐analysis of a large number of publications reporting tolerance phenotypes of plants overexpressing exchangers of the cation/proton antiporter 1 family (CPA1, which includes NHX proteins) concluded that the transgenic effect on K status was generally more pronounced than on Na content (Ma et al ). Indeed, AtNHX1 catalyzes K/H and Na/H exchange in biochemical assays with purified vacuoles (Venema et al , Hernandez et al ), and a reverse genetic approach has conclusively shown that the main role for Arabidopsis transporters AtNHX1 and AtNHX2 is the thermodynamically active accumulation of K in cell vacuoles (Bassil et al , Barragan et al , Andres et al ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation